Dal voto alla valutazione per l'apprendimento - Cristiano Corsini; Carla Gueli (LED Edizioni Universitarie, 2022)
This paper returns the outcomes of a research-training project, as result of the collaboration between university researchers and teachers and principals of a network of schools in Lazio. Research-training is a way of doing empirical research that, making use of differentiated methodologies aims to develop teaching professionalism through the construction of research paths agreed between universities and schools. The present investigation started from a training need made explicit by schools: the need to develop skills useful for dealing with the transition from grades to judgments. A synthesis of teachers' diverse views on assessment and perceptions of change is proposed here. The reflection and evidence gathered can help to prefigure the direction to be taken to overcome the risk that the use of feedback or levels may trace a construct that refers to the grade, de-emphasizing or effectively nullifying its value. Feedback and restitution, on the other hand, are tools of a motivating design that aims to provide learners with guidance for understanding and analysing their own learning and support for making effective and conscious choices in organising future learning.